Exigências nutricionais e estudo da relação entre a termografia infravermelha e a produção de calor de touros Angus e Nelore - Gomes, Rafael Aparecido (2016)
In this study, we used 32 animals with initial body weight (BW) of 380 ± 5.2 kg to determine the nutritional requirements of Nellore and Angus young bulls using the comparative slaughter technique. At the beginning of the experiment, four animals of each breed were slaughtered. The remainder were housed in individual stalls, in which eight animals of each breed were fed ad libitum a silage/concentrate (SC) diet (300 g/kg of silage and 700 g/kg of a concentrate based on corn and soybean meal, DM basis). Another 4 animals of each breed were fed the SC diet at 55% of dry matter intake adjusted for the metabolic BW of the animals that received the SC diet ad libitum. We measured daily intake, and conducted a metabolism trial with total collection of feces and urine. The data were used to estimate metabolizable energy intake. On the 25 th , 50 th and 75 th experimental days, infrared thermal images were taken of the faces of animals fed ad libitum to access skin and ocular surface temperatures. A metabolism trial was conducted to estimate metabolizable energy intake. After 84 experimental days, the cattle were harvested in order for us to calculate retained energy and heat production (HP). The data were analyzed using SAS. The nutritional requirements were calculate using GLM and NLIN procedures. The relation between infrared thermography and HP was studied using the MIXED and REG procedures. The net energy requirements for maintenance differed between Angus and Nellore, with 98 and 76 kcal/kg EBW 0.75 ·d -1 , respectively, when calculated by logarithm model, and 100 and 80 kcal/kg EBW 0.75 ·d -1 , respectively, when calculated by nonlinear model. There was no difference between breeds regarding nutritional requirements for growth. We found significant correlations (P 0.005) between daily HP and maximum (r= 0.65) and average skin temperatures (r = 0.65) and maximum (r = 0.65) and average ocular surface (r= 0.69) temperatures recorded on d 50. The results indicate that Zebu bulls have lower net energy requirements for maintenance than Bos taurus taurusbulls and that Infrared thermography has potential for the evaluation of cattle HP.